Pervasive Computing Paradigms for Mental Health 5th International Conference, MindCare 2015, Milan, Italy, September 24-25, 2015, Revised Selected Papers - Serino, Silvia; Matic, Aleksandar; Giakoumis, Dimitris; Lopez, Guillaume; Cipresso, Pietro (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the 5th International Conference on Pervasive Computing Paradigms for Mental Health, MindCare 2015, held in Milan, Italy, in September 2015. The 23 full papers and 6 short papers presented were carefully reviewed and selected from 40 submissions. The papers deal with the use of technologies in favor of maintaining and improving mental wellbeing. They focus on building new computing paradigms and on addressing a multitude of challenges in mental healthcare, for example in psychiatric and psychological domains with emphasis on new technologies, such as video and audio technologies and mobile and wearable computing.